Developing Financial Literacy Storybooks for Junior High School Students: A Fuzzy Delphi Need Analysis - Okto Irianto; Susanto; Henie Poerwandar Asmaningrum; Daud Andang Pasalli (Didaktika: Jurnal Kependidikan, 2025)
This study conducted a needs analysis for the development of financial literacy storybooks for junior high school students on the Story Jumper platform, using the Fuzzy Delphi method. A panel of 10 experts, including financial educators, curriculum developers, educational technologists, and professional storytellers, was formed and consulted through three rounds. The study revealed eight priority content areas in financial literacy: first comes Saving Wisely (93.3%), followed by Managing Expenses (90.0%), and Understanding Money and Credit (86.7%). The most significant expectancies mentioned are elements of storytelling such as interactive decision points (93.3%) and relatable characters: teenage protagonists (86.7%) essential for engaging students and enhancing learning. Guidelines for implementation stipulated the optimum duration for a story of 15 to 20 minutes, adding interactive elements every 3-4 pages and visual elements such as drawings every 2-3 pages. The compatibility assessment unveiling the extent of Story Jumper found that it is very aligned with visual storytelling (0.92) but limited in as far as complex financial calculations (0.71). While this study offers considerably useful guidelines for the incorporation of financial literacy storybooks into the educational setups, the following isolated limitations require further search. These include reliance on expert opinion, no classroom trials, limited cultural context appraisal, and lack of longitudinal studies. All in all, this study therefore illuminates the potential of digital storytelling as an innovative pedagogical approach for teaching financial literacy and provides practical advice to educators and program developers while setting the stage for future investigations and refinements of these resources.